2016
DOI: 10.1111/odi.12540
|View full text |Cite
|
Sign up to set email alerts
|

Chronic orofacial pain

Abstract: The issues specific to trigeminal pain include the complexity of the region, the problematic impact on daily function and significant psychological impact (J Dent, 43, 2015, 1203). By nature of the geography of the pain (affecting the face, eyes, scalp, nose, mouth), it may interfere with just about every social function we take for granted and enjoy (J Orofac Pain, 25, 2011, 333). The trigeminal nerve is the largest sensory nerve in the body, protecting the essential organs that underpin our very existence (b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 27 publications
(59 reference statements)
0
18
0
Order By: Relevance
“…Animals subjected to IoN-CCI display behavioral phenotypes consistent with clinical symptoms caused by trigeminal nerve injury 21 . The improved dIoN-CCI surgical procedure is more suitable for studying trigeminal neuropathic pain.…”
Section: Discussionmentioning
confidence: 94%
“…Animals subjected to IoN-CCI display behavioral phenotypes consistent with clinical symptoms caused by trigeminal nerve injury 21 . The improved dIoN-CCI surgical procedure is more suitable for studying trigeminal neuropathic pain.…”
Section: Discussionmentioning
confidence: 94%
“…Currently, dentists are facing increasing challenges from geriatric and special needs patients who suffer from psychiatric and neurological (particularly neurodegenerative) diseases . A greater effort is demanded for dental researchers to translate their research findings to clinical practice to achieve better diagnoses, treatments and outcome evaluations.…”
Section: Introductionmentioning
confidence: 99%
“…The focus was placed on MRI‐based neuroimaging methods, which have been the predominant methods of brain imaging used in dental research. It is noteworthy that this article did not aim to provide a full review of all the neuroimaging studies of oral functions, or summarise the mechanisms underlying oral diseases (but see Refs for a detailed review on this aspect). The article consists of the following sections: Two clinical examples, mastication and dental fear, are presented to highlight the advantages of using neuroimaging to unravel the association between the brain and oral behaviours of the patients. The general pros and cons of neuroimaging—focusing on MRI‐based neuroimaging methods—are presented.…”
Section: Introductionmentioning
confidence: 99%
“…It is a common condition; studies in Brazil [3] and Hong Kong [4] found that over 40% of the population had experienced orofacial pain. Because of the complexity of the affected regions, orofacial pain can have a deleterious effect on the patients' daily functions (including eating, drinking, and speaking) and can seriously affect various social functions and the quality of life [5,6].…”
Section: Introductionmentioning
confidence: 99%